Effects of sandblasting and acid etching on the surface properties of additively manufactured and machined titanium and their consequences for osteoblast adhesion under different storage conditions - Akbas, Osman; Gaikwad, Amit; Reck, Leif; Ehlert, Nina; Jahn, Anne; Hermsdorf, Jörg; Winkel, Andreas; Stiesch, Meike; Greuling, Andreas (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionAdditive manufacturing (AM) enables the production of complex, patient-specific titanium implants. However, the as-built surfaces of AM parts often require postprocessing to enhance surface properties for optimal osseointegration.MethodsThis study investigates the effects of varying sandblasting pressures (2 bar vs. 6 bar) and subsequent acid etching (SAE) on the surface properties of additively manufactured and machined titanium (Ti-6Al-4V and commercially pure titanium (cp-Ti), respectively). While changes in surface roughness and morphology were assessed at different process stages using optical profilometry and scanning electron microscopy, the analyses of surface wettability (contact angle measurement) were focused on effects after SAE and during different storage conditions (ambient air vs. NaCl). The resulting differences in material properties were then evaluated for their biological impact on osteoblast compatibility. For this purpose, the parameters cell adhesion, morphology, and membrane integrity were investigated using confocal laser microscopy and LDH assay.ResultsInitial high roughness of AM titanium surfaces was decreased by sandblasting, while initial smooth machined surfaces (MM) increased in roughness. Acid etching introduced characteristic irregular patterns on the surface with only marginal consequences for the resulting overall roughness. While all surfaces demonstrated high hydrophilicity directly after etching, storage under ambient air increased hydrophobicity over time, while NaCl storage preserved hydrophilicity and improved biocompatibility marginally. Osteoblast adhesion and morphology were optimal only under no storage condition, with uncompromised membrane integrity.DiscussionNotably, the biological consequences observed for MM and AM titanium were rather similar, considering the differences in used materials, production techniques, and subsequent surface morphologies. Carefully applied SAE can also optimize the surface characteristics of additive manufactured titanium for an improved implant performance, with storage conditions critically influencing surface wettability and bioactivity.